Chandrabala Modi Academy, Ankleshwar (B) - Dixit, Mukund, (SAGE Knowledge. Cases., 2006)
The Chandrabala Modi Academy (B) case has been written to discuss the role of the Leader. In this example the principal of Chandrabala Modi Academy Mr. Bhattacharya is used to stress the role of a leader as a reviewer and restrategiser. As a reviewer Mr. Battacharya is required to assess what has happened in the school thus far and develop guidelines for the future. As a restrategiser he is required to reformulate a strategy for the school in the context of past experience and possible developments in the future. The case stresses the need for a leader to develop a framework for reviewing the past activities and reformulating a strategy for the future.